Improving inter-fiber bonding by cellulase under a high surface lignin level - Jinglei Xie; Shijie Liu (Results in Surfaces and Interfaces)
Lignin is behaving negatively in cellulase hydrolysis, leading to the high cost of cellulase in many areas. Instead of removing lignin, the fiber surface composition was changed in structure and distribution in this work through a light mechanical refining. 2 h of cellulase adsorption and hydrolysis were performed after that. The cellulase hydrolysis was found to be improved with the glucose production increasing from 0.031 to 0.074 g L−1. Hydrolyzed fibers were then made into handsheet for inter-fiber bonding properties characterization. With most lignin retained and more hydrogen bonding formed, both tensile index and zero-span tensile index were found to be improved after the cellulase modification. It can be concluded that the cellulase hydrolysis of fibers is positively correlated with the inter-fiber bonding properties.